2019
DOI: 10.1055/s-0039-1688999
|View full text |Cite
|
Sign up to set email alerts
|

Use of Neonatal Lung Ultrasound for the Early Detection of Pneumothorax

Abstract: Objective Pneumothorax (PTX) can be diagnosed using lung ultrasonography (LUS) in adult patients, but there are only a few reports of LUS in PTX diagnosis in neonates. The aim of the study was to assess the diagnostic accuracy for PTX. Study Design This was a retrospective review study performed in our neonatal intensive care unit (level III) between June 2015 and June 2018. All eligible patients underwent an LUS scan before undergoing a chest X-ray (CXR), which was considered the reference standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…LUS for the diagnosis of neonatal PTX is a manageable and timely diagnostic modality 17,19,20,21,22,23,30,35,36,37,38 . Recent animal studies found that the LUS diagnosis of PTX is very accurate and reliable 39,40 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…LUS for the diagnosis of neonatal PTX is a manageable and timely diagnostic modality 17,19,20,21,22,23,30,35,36,37,38 . Recent animal studies found that the LUS diagnosis of PTX is very accurate and reliable 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…In one of these studies LUS and chest X-rays findings of PTX were compared to CT scans as a point of reference and confirmed that LUS is superior to chest X-rays in diagnosis of small PTXs 40 . In newborn infants with PTX, LUS sensitivity and specificity are also higher than that of chest X-rays 17,[19][20][21][22][23]37,38 , and recent meta-analysis further established that the sensitivity of LUS in diagnosing PTX is nearly 50% higher than the chest X-ray sensitivity 41,42 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations